2015
DOI: 10.7554/elife.06513
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent electroencephalogram (EEG) patterns during sevoflurane general anesthesia in infants

Abstract: Electroencephalogram (EEG) approaches may provide important information about developmental changes in brain-state dynamics during general anesthesia. We used multi-electrode EEG, analyzed with multitaper spectral methods and video recording of body movement to characterize the spatio-temporal dynamics of brain activity in 36 infants 0–6 months old when awake, and during maintenance of and emergence from sevoflurane general anesthesia. During maintenance: (1) slow-delta oscillations were present in all ages; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 54 publications
12
105
0
1
Order By: Relevance
“…The low frequency range is the dominant rhythm in infants up to 1 year of age. This was also observed in newborns of 0-3 months or 4-6 months of age (Cornelissen et al, 2015), however, no significant frontooccipital power differences were found at any frequency in infants at 0-3 months of age (Cornelissen et al, 2015). This result supports that coherence patterns differ between brain regions at birth, since coherence was higher in the frontal vs. occipital region of the brain.…”
Section: Discussionsupporting
confidence: 72%
“…The low frequency range is the dominant rhythm in infants up to 1 year of age. This was also observed in newborns of 0-3 months or 4-6 months of age (Cornelissen et al, 2015), however, no significant frontooccipital power differences were found at any frequency in infants at 0-3 months of age (Cornelissen et al, 2015). This result supports that coherence patterns differ between brain regions at birth, since coherence was higher in the frontal vs. occipital region of the brain.…”
Section: Discussionsupporting
confidence: 72%
“…Spectrograms were computed with the multitaper method (18) (Code available at Chronux). To assess statistical significance for the difference in spectra at each frequency, we computed the 99% confidence intervals by using a published bootstrap algorithm (58,59). Only the frequencies whose confidence intervals did not include zero within at least one complete bandwidth unit (3 Hz for spectra and 1.5 Hz for coherence) were considered to be statistically significant (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Most pediatric EEG studies have been performed with a limited number of EEG channels, or with variability in types of montages and analytical methods used; few have evaluated EEG in the first year of life (7)(8)(9)(10)(11)(12)(13)(14). Spatial and temporal aspects of discontinuity events and clinical correlates have not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%